Major Challenges and Future Approaches in the Employment of Blockchain and Machine Learning Techniques in the Health and Medicine. (10th June 2022) - UmaMaheswaran, S. K.; Prasad, G. Lakshmi Vara; Omarov, Batyrkhan; Abdul-Zahra, Dalael Saad; Vashistha, Piyush; Pant, Bhasker; Kaliyaperumal, Karthikeyan
Abstract : According to the benefits in safeguarding and transferring medical information, illness assessment, evaluation of "Magnetic Resonance Mapping" images, and certain other disciplines, blockchain and machine learning (ML) technology has significantly piqued attention in the healthcare domains. Formerly, those chores have been performed out along with individuals; eventually, individuals acquired attraction because to its precision and efficiency. The proposed study will examine the activities and possible capabilities of learning algorithms and blockchain in the healthcare professions focusing on these fascinating facts. Primary and secondary data analysis has been executed, with primary analysis method consisting of a survey of 150 randomly picked medicine professionals with expertise in machine learning and blockchain. They gave their answers that were being subsequently transferred to figures and employed as response variable in SPSS examining. The length of time where learning and blockchain have been used in medicine is really the independent factor. To better understand the primary and small hurdles of integrating machine learning and blockchain, a correlation investigation was done. Thereafter, secondary methodology is employed to validate the primary study results.